Dental Age Estimation of Indonesian Population : A Literature Review - Rosalina Intan Saputri (Maranatha Christian University, 2020)
Age is one of the important parts of the identification process, which is an requirement in legal framework, criminal investigation, and, in health care, to provide significant information for diagnosis and treatment planning. Age estimation is a major study in forensic, especially when the information related to the deceased is unavailable. Dental is one of the strong variables which could be used in estimating the age of living or deceased. Dental age estimation methods were mainly based on the changes in tooth development which influenced by diverse internal and external factor. Therefore, studies of dental age estimation of various population were resulted different discrepancies. This paper reviews about studies of dental age estimation specifically in Indonesian population, including the population age, age estimation methods, study sample, and studies’ findings.